P3.168 Evaluation of the point-of-care xpert® CT/NG and osom® trichomonas rapid tests against the anyplex™ii STI-7 detection assay. (8th July 2017) - Mitchev, Nireshni; Singh, Ravesh; Naidoo, Jessica; Osman, Farzana; Samsunder, Natasha; Garrett, Nigel; Mlisana, Koleka
Abstract : Introduction: Syndromic management of sexually transmitted infections (STIs), as practised in most poorly resourced countries misses out asymptomatic infections. Affordable nucleic acid amplification tests (NAATs) are needed for accurate STI diagnosis and treatment. Methods: As part of a cohort study assessing a diagnostic STI care model among young South African women presenting for syndromic care, we evaluated the clinic-based point-of-care (POC) tests Xpert CT/NG and OSOM Trichomonas Rapid Test against the laboratory-based Anyplex II STI-7, a multiplex real-time PCR assay which detects Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV), M. genitalium (MG), M. hominis (MH), U. urealyticum (UU) and U. parvum (UP) in a single reaction. All positive and discordant results were confirmed with a third molecular assay, the FTD STD9. Results: Vaginal swabs taken from 247 women were assessed in parallel. 238 of 247 (96.4%) results were in agreement comparing Xpert and Anyplex. All nine discrepant results were positive for CT on Xpert but negative on Anyplex. FTD STD9 confirmed three positive and six negative results. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of Xpert for CT against the two assays was 100%, 97.1%, 86.0%, 100%, respectively; and for NG 100%, 99.6%, 92.3%, 100%. The sensitivity, specificity, PPV and NPV of OSOM for TV against the two assays was 77.8%, 100%, 100%, 99.2%. In addition to the CT, NG and TV detection, the Anyplex identified a prevalence of 4.8% MG, 33.5% MH, 19.1% UU and 51.4% UP in this population. Conclusion: The overall performance of Xpert CT/NG against laboratory-based assays was comparable. A lower PPV may lead to some overtreatment, however, in a high burden STI and HIV region, where STIs are often asymptomatic, the high sensitivity and specificity are reassuring. The widened spectrum of Anyplex targets highlights the high burden of Ureaplasma and Mycoplasma species in this setting, whose clinical significance need further exploration.